Interval symmetric single-step procedure ISS2-5D for polynomial zeros - Noraini Jamaludin; Mansor Monsi; Nasruddin Hassan (Universiti Kebangsaan Malaysia, 2014)
We analyzed the rate of convergence of a new modified interval symmetric single-step procedure ISS2-5D which is an extension from the previous procedure ISS2. The algorithm of ISS2-5D includes the introduction of reusable correctors δi(k) (i = 1, …, n) for k ≥ 0. Furthermore, this procedure was tested on five test polynomials and the results were obtained using MATLAB 2007 software in association with IntLab V5.5 toolbox to record the CPU times and the number of iterations.